Seguimiento ecográfico de la involución uterina posparto en alpacas (Vicugna pacos) - Cabezas-García, Edward Hernando (2025)
Uterine involution in alpacas has been described anatomically and histologically; however, the relationship of postpartum morphometric variation in vivo is unknown. The aim of this work was to describe the morphometric changes in the uterus of alpacas associated with postpartum involution, using transrectal ultrasound (B mode). For this purpose, 38 Huacaya alpacas were distributed into three groups: 1. Primiparous (n=14), 2. Multiparous (n=16) with measurements every 5 days from day 5 postpartum (DPP) to 30 DPP, and 3. Control (n=8) with completed uterine involution (40 DPP). A Chison EcoVet 6® ultrasound system with a 7 MHz transducer was used. The variables were uterine diameter (UD, cm), uterine wall thickness (UWT, cm) and uterine area (UA, cm2). The effect of DPP was assessed by one-way analysis of variance. UA was significantly higher for multiparous alpacas compared to primiparous ones. UA was influenced by DPP (primiparous and multiparous; p<0.001), whereas UA was significant only for multiparous ones (p<0.001). In both groups, UWT showed higher variability compared to UD and UA, respectively. The UD curve indicates that uterine involution is complete after 20 DPP (primiparous and multiparous). The presence of intrauterine fluids was detected up to day 18 DPP. It is concluded that ultrasound evaluation of variables can help describe the moment in which postpartum uterine involution is completed in alpacas.